1984
DOI: 10.1530/jrf.0.0720311
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Poisson distribution theory in analysing the interaction between human spermatozoa and zona-free hamster oocytes

Abstract: Summary. The value of Poisson distribution theory in describing and predicting the nature of sperm\p=n-\egg interaction in vitro has been investigated using an interspecific i n\ x=r eq-\ vitro fertilization system, incorporating zona-free hamster oocytes and human spermatozoa. The frequency distribution of polyspermic oocyte penetrations in 72 experiments exhibited good agreement with the Poisson distribution at all levels of fertilization, indicating that each oocyte must be of equal penetrability and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Furthermore, analysis of the in-vitro penetration data using the Poisson model described by Aitken & Elton (1984) has emphasized that the impaired penetration rates observed with these asthenozoospermic patients is not simply a consequence of the reduced numbers of motile sperm¬ atozoa because when the results were corrected to a constant concentration of motile cells, there were still differences between the asthenozoospermic patients and the normal fertile controls. Although no assessments of the quality of sperm movement were made in this study we have previously shown that the movement characteristics exhibited by human spermatozoa have little impact on the aspects of sperm function measured by the penetration test (Aitken et al, 1983a(Aitken et al, , 1985.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, analysis of the in-vitro penetration data using the Poisson model described by Aitken & Elton (1984) has emphasized that the impaired penetration rates observed with these asthenozoospermic patients is not simply a consequence of the reduced numbers of motile sperm¬ atozoa because when the results were corrected to a constant concentration of motile cells, there were still differences between the asthenozoospermic patients and the normal fertile controls. Although no assessments of the quality of sperm movement were made in this study we have previously shown that the movement characteristics exhibited by human spermatozoa have little impact on the aspects of sperm function measured by the penetration test (Aitken et al, 1983a(Aitken et al, , 1985.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study (Aitken & Elton, 1984) ( -rm) where r = the ratio of the theoretical concentration of motile spermatozoa to the observed concentration in the assay. In the present study this formula was used to correct each result obtained with the hamster oocyte assay to that which would have been observed at a fixed motile sperm concentration of 5 106/ml.…”
Section: Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assay was performed using a total sperm concentration of 10 106 spermatozoa/ml and the results were subsequently adjusted for a standard concentration of 5 106 motile spermatozoa/ml. This correction was based upon the formula described by Aitken & Elton (1984) + was assessed by monitoring the fluorescence signal emitted by the Ca2+ chelating agent, Quin-2, as described by Tsien, Pozzan & Rink (1982). The spermatozoa were washed 3 times with Medium BWW, and finally resuspended at a total sperm concentration of 20 106/ml.…”
Section: Methodsmentioning
confidence: 99%